2022
DOI: 10.1177/03635465221131984
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Patients’ Understanding of Sling Necessity and Home Assistance on Sling Wear After Shoulder Surgery

Abstract: Background: Perioperative education and socioeconomic factors influence patient behavior. Recent evidence has suggested that sling compliance is associated with improved outcomes after shoulder surgery; it is important to investigate factors that influence sling compliance. Purpose: To determine the associations between postoperative sling wear and patients’ understanding of sling necessity, postoperative home assistance, and social deprivation. Study Design: Cohort study; Level of evidence, 2. Methods: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The authors reported that self-reported adherence was significantly less than the sensor-measured adherence and concluded self-reported adherence is unreliable [21]. Another prospective study by Livesey et al assessed sling wear adherence in 66 post-operative shoulder patients for one month after their procedures using similar temperature sensors [22]. The study aimed to evaluate the associations between postoperative sling wear adherence and patients' understanding of sling necessity, postoperative home assistance, and social deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that self-reported adherence was significantly less than the sensor-measured adherence and concluded self-reported adherence is unreliable [21]. Another prospective study by Livesey et al assessed sling wear adherence in 66 post-operative shoulder patients for one month after their procedures using similar temperature sensors [22]. The study aimed to evaluate the associations between postoperative sling wear adherence and patients' understanding of sling necessity, postoperative home assistance, and social deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…In their study in this issue of the AJSM , Livesey and colleagues 8 set out to determine whether patients’ understanding of the reasons for wearing a sling correlated with their actual use of this device. Note that they were not seeking to determine whether sling wear influenced the outcomes of surgery, just whether the patients followed the surgeons’ instructions.…”
mentioning
confidence: 99%